PERANAN GEREJA DALAM PENGUATAN NILAI-NILAI PANCASILA PADA JEMAAT DITENGAH MASYARAKAT PLURALISME - Natanael Sitinjak; Ana Mentari; Edi Siswanto; M. Mona Adha; Abdul Halim (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
Indonesia is a country with a high level of diversity in terms of ethnicity, culture, religion, and language, which necessitates the strengthening of Pancasila values to maintain harmony and unity. However, in the era of globalization and digitalization, the internalization of Pancasila values still faces various challenges, including within religious institutions. This study aims to analyze the role of the Pentecostal Church in Indonesia (GPdI) El-Shaddai Purbolinggo, East Lampung, in strengthening Pancasila values within a pluralistic society. This research employs a descriptive qualitative approach, with data collection techniques including interviews, observations, and documentation. The theoretical framework is based on structural functionalism, social construction, and role theory, which position the church as an agent of socialization and value transformation within society. The findings reveal that GPdI El-Shaddai Purbolinggo plays an active role as a social transformation agent by integrating Pancasila values into worship activities, sermons, faith education, and social services. The process of internalizing these values is carried out not only cognitively but also through social practices, interactions, and the exemplary conduct of church leaders in the daily lives of congregants. Sociologically, these findings indicate that the church makes a significant contribution to strengthening social cohesion, solidarity, and tolerance within a pluralistic society. The implications of this study emphasize that reinforcing Pancasila values is not solely the responsibility of the state but also requires the active involvement of religious institutions as strategic actors in fostering social integration and sustaining national unity.